Selected Management Concepts in Supply Chains - Łukiewska, Katarzyna; Wieczorek, Adam; Łada, Magdalena (Olsztyn Economic Journal, 2021)
Supply chain management is considered a complex process that can lead to errors, conflicts, or a breakdown of cooperation. In chain creation, it is important to organize and rationalize the network of interconnections to which the assumptions of concepts, such as lean manufacturing, agile manufacturing, and resilient supply chains, can be applied. For this reason, the aim of the research presented in the study was to attempt to identify how selected management systems in supply chains can influence the improved functioning of enterprises in a vulnerable condition and in the contemporary challenging situation. The starting point for consideration was to define the concept of a supply chain, lean manufacturing, agile manufacturing, and resilient supply chains, and to indicate the benefits of using the selected concepts. For this purpose, foreign and domestic literature was used. The result is a description, analysis, and criticism of the different systems in relation to the supply chain.